iNaturalist mammal observations classified by evidence type - Mohammad Alyetama; Alex J. Jensen; Yakira Jackson; Jane Widness; Roland Kays; Benjamin R. Goldstein (PLoS ONE, 2026)
Ecologists show growing interest in observational data generated by citizen scientists. For mammals, the largest citizen science platform is iNaturalist, which has more than 5 million Research Grade observations globally represented through images of living animals, dead animals, tracks, and scat. These different types of evidence could give insight into the underlying sampling paradigm for an observation (e.g., dead animals might be more likely to be reported near roads) and thus may be useful for scientific applications of these data. However, while iNaturalist allows users to annotate observations by evidence type, many observations are not annotated. We use machine learning to classify the evidence types associated with observations of North American mammals in iNaturalist, adding metadata that can be used to subset data or to model multiple observation processes. Here, we present a dataset containing metadata augmenting 1.33 million North American mammal iNaturalist observations with evidence type. Each observation is categorized as either live animal, dead animal, tracks, scat, or other sign, and an associated confidence score is provided.